Prevalence of lower urinary tract symptoms in Vilnius area children and adolescents - Jankauskienė, Augustina; Vaičiūnienė, Daiva; Stacevičienė, Indrė (Acta medica Lituanica, 2014)
Background. Lower urinary tract symptoms are a common problem worldwide among children. The aim of the study was to evaluate how common lower urinary tract symptoms are among children and adolescents in the Vilnius area. Materials and methods. A cross-sectional study comprised 360 children (5–11 years) and 388 adolescents (12–18 years) who were hospitalized at the Children’s Hospital or referred for consultation for different health reasons not related to urination problems. Data were obtained by using a self-administered anonymous questionnaire. The data were compared between gender (344 boys and 404 girls) and age groups (children and adolescents). Results. Only a half (55.7%) of all questioned children and adolescents had no lower urinary tract symptoms. Nocturnal enuresis (NE) was found in 8.7%, urgency in 34.0% and daytime wetting in 24.6% of the questioned children and adolescents. Monosymptomatic NE accounted for 20.0% of NE. Secondary NE was seen in a quarter (24.5%) of children with NE. Lower urinary tract symptoms were more prevalent in children compared to adolescents (56.1% vs 38.1%, p = 0.000). There were no significant differences between genders except urgency, which was more frequent in girls (29.4% vs 37.9%, p = 0.014). Conclusion. Lower urinary tract symptoms are frequent in children and adolescents in the Vilnius area, so they need greater attention by healthcare providers.
Keywords: children; adolescents; lower urinary tract symptoms; nocturnal enuresis